"Good Athletes Have Fun": a Foucauldian reading of university coaches' uses of fun. Issue 1 (2nd January 2019) - Avner, Zoe; Denison, Jim; Markula, Pirkko
Abstract: Fun is deeply ingrained in the ways we talk about and understand sport: Having fun is what makes sport positive and healthy. Drawing on a Foucauldian perspective, we problematize how fun, a psychological construct, informs coaches' practices. Interviews with 10 varsity coaches from a Canadian university indicated that the coaches used fun to overcome the 'grind' of physical skill training. In addition, fun was used to develop and naturalize a need for athletes' positive psychological traits and skills. In their training contexts, thus, the coaches clearly employed fun to reinforce their use of a number of dominant disciplinary training practices. As a result, instead of operating as a positive force for athlete engagement, the incorporation of fun further legitimized and perpetuated coaches' 'normal' training practices.